Comment on “The concept of ritual in Confucian thought and its implications for social order” - Wu, Xia (2024)
Commented article: WU, X. Y; ZHAO, Y. The concept of ritual in Confucian thought and its implications for social order. Trans/Form/Ação: Unesp journal of philosophy, vol. 47, n. 6, e02400331. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/16348.